Silicato de potássio em substituição ao cloreto de potássio na cultura do algodão - Tiago da Silva Rodrigues (2022)
High concentration and solubility make KCl the main source of potassium used in Brazilian agriculture, which has generated high import costs and concerns regarding the impacts of this source on the soil microbiota. Potassium silicate has been studied as an alternative to KCl. The general objective of this work was to evaluate the effects of replacing potassium chloride with potassium silicate from phonolite rock powder on cotton production parameters, and its dynamics on nutritional and microbiological aspects of the soil. Thus, this work is composed of two chapters, which describe (I) the efficiency of sources for potassium nutrition in the cotton crop; and (II) the dynamics of potassium in the soil through topdressing with a soluble and alternative source. For this, an experiment was installed in the 19/20 summer crop, in the municipality of Chapadão do Sul - MS, where two sources of potassium fertilization (potassium chloride (KCl) and potassium silicate) were evaluated, combined with five doses of supply of topdressing fertilization, being: 0, 80, 170, 250 and 300 kg of K2O ha-1. In Chapter I, the production components were evaluated: plant height, initial and final plant population, weight of ten medium bolls and ten bolls per third of the plant (lower, medium and upper), seed cotton productivity, fiber productivity and fiber yield. In chapter II, the following were evaluated: potassium dynamics in the soil surface layers stratified every 5 cm (0-5; 5-10; 10-15 and 15-20), potassium accumulation in leaf tissue, and abundance of nitrifying bacteria based on quantification of amoA genes. The results obtained for most items do not differ, showing potential silica as an alternative for a replacement with relevant nutritional characteristics in relation to the present work. Ten boll weight for the main performance effect, and for cotton production mainly for the sensitization effect. For the potassium contents in the soil, the layer of 0-10cm both differences of dose increase, for the layer of 10-15cm the KCl even presented better performance in availability and response to the dose increment, being that of 15-20 both sources did not differ statistically. The best foliar accumulation was also obtained with the use of KCl, responding linearly to the increase in the dose. As for the group of nitrifiers, the damage to the microbiota was accentuated when KCl was used, and the potassium silicate was similar without power, evidencing that it did not cause control to this community.